The Vital Role of Diabetes Nurse Educators in Smoking Cessation: A Case Study from Türkiye - Özcan, Şeyda; Çarkoğlu, Aslı; Nichter, Mimi; Nichter, Mark; Aydın, Nuran (Addicta: The Turkish Journal on Addictions, 2023)
This paper discusses the development and implementation of a smoking cessation training program for diabetes nurse educators. People with diabetes who smoke have a significantly higher risk of morbidity and mortality. Smoking greatly increases diabetes complications. Surveys were conducted to ascertain how frequently nurses counseled patients to quit and their interest in cessation training. Observations of nursepatient interactions and interviews with diabetes nurses facilitated the development of a culturally sensitive cessation training program. Survey results revealed that diabetes nurse educators recognized the need for training in smoking cessation, as many patients with diabetes do not consider smoking to be harmful for their health. A two-day workshop was developed for nurses on the specific harms of smoking for diabetes patients, including hands-on training in cessation counseling and motivational interviewing. Two months after training, nurses reported that the skills they acquired gave them confidence to counsel patients but identified four challenges to conducting cessation in their clinical settings. Diabetes nurse educators can play a pivotal role in delivering cessation. Training and overcoming challenges to implementation are urgently needed in the time of coronavirus disease 2019 given the dual risks of diabetes and smoking for severe complications
Keywords: Diabetes and tobacco; diabetes nurses; nurses in cessation; smoking cessation; tobacco control